2014
DOI: 10.1097/mnm.0000000000000052
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of PET measurement for presynaptic dopaminergic functions using L-[β-11C]DOPA and [18F]FE-PE2I in humans

Abstract: We found good test-retest reproducibility for the kref values of L-[β-(11)C]DOPA and that for the BPND of [(18)F]FE-PE2I in the striatum and midbrain, indicating the reliability of clinical investigation using PET with L-[β-(11)C]DOPA and [(18)F]FE-PE2I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 13 publications
1
30
2
Order By: Relevance
“…The cerebellum was found to be a suitable reference region because no statistically significant differences of V T AUC ratio were found between controls and PD patients. In healthy subjects, it has been shown that SRTM is a suitable and reliable quantification method (21,22). Because parametric imaging is based on the use of LoganRef, we first compared LoganRef applied at the ROI level with SRTM and found an excellent correlation of BP ND for all subjects examined.…”
Section: Quantification Of 18 F-fe-pe2imentioning
confidence: 97%
See 1 more Smart Citation
“…The cerebellum was found to be a suitable reference region because no statistically significant differences of V T AUC ratio were found between controls and PD patients. In healthy subjects, it has been shown that SRTM is a suitable and reliable quantification method (21,22). Because parametric imaging is based on the use of LoganRef, we first compared LoganRef applied at the ROI level with SRTM and found an excellent correlation of BP ND for all subjects examined.…”
Section: Quantification Of 18 F-fe-pe2imentioning
confidence: 97%
“…In nonhuman primates, 18 F-FE-PE2I displays a high target-to-background ratio, fast washout from the brain, early peak equilibrium, and a favorable metabolic profile (17)(18)(19)(20). In addition, initial studies in healthy subjects have shown that the quantification of 18 F-FE-PE2I binding to the DAT can be accurately and reliably performed using the simplified reference tissue model (SRTM) with the cerebellum as a reference region (21,22). The aim of this study was to examine the suitability of 18 F-FE-PE2I as a tool for imaging the nigrostriatal pathway in PD.…”
mentioning
confidence: 99%
“…Several studies have demonstrated the utility of DAT imaging in clinical applications, and numerous SPECT and PET radioligands targeting the DAT have been developed (12). 18 F-(E)-N-(3-iodoprop-2-enyl)-2b-carbofluoroethoxy-3b-(49methylphenyl)nortropane ( 18 F-FE-PE2I) is a radioligand for the DAT recently developed at the Karolinska Institutet PET Centre. In nonhuman primates, 18 F-FE-PE2I showed favorable kinetic properties, such as high target-to-background ratio, fast washout from the brain, early peak equilibrium, and favorable metabolic profile, with less abundance of radiometabolites that could cross the blood-brain barrier.…”
mentioning
confidence: 99%
“…18 F-(E)-N-(3-iodoprop-2-enyl)-2b-carbofluoroethoxy-3b-(49methylphenyl)nortropane ( 18 F-FE-PE2I) is a radioligand for the DAT recently developed at the Karolinska Institutet PET Centre. In nonhuman primates, 18 F-FE-PE2I showed favorable kinetic properties, such as high target-to-background ratio, fast washout from the brain, early peak equilibrium, and favorable metabolic profile, with less abundance of radiometabolites that could cross the blood-brain barrier. 18 F-FE-PE2I showed in vitro and in vivo selectivity for the DAT as compared with other monoaminergic transporters, as well as a suitable affinity for the DAT (12 nM measured in vitro) (13)(14)(15).…”
mentioning
confidence: 99%
See 1 more Smart Citation